2019
DOI: 10.3390/nu11061273
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis and Prematurity: Is There a Role for Probiotics?

Abstract: Healthy microbiota is a critical mediator in maintaining health and it is supposed that dysbiosis could have a role in the pathogenesis of a number of diseases. Evidence supports the hypothesis that maternal dysbiosis could act as a trigger for preterm birth; aberrant colonization of preterm infant gut might have a role in feeding intolerance and pathogenesis of necrotizing enterocolitis. Despite several clinical trials and meta-analyses, it is still not clear if modulation of maternal and neonatal microbiota … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 107 publications
(107 reference statements)
0
36
1
2
Order By: Relevance
“…Concentration of Goji berry polyphenols and carbohydrates in liquid and dried-encapulated Goji berry extract (LGBE and DGBE, respectively), as well as maltodextrin or SiO2 concentration added in liquid Goji berry extracts (LGBE) before encapsulation of the three samples of dried-encapsulated Goji berry powder used in this study. 19.69 ± 0.49 0.65 ± 0.11 3 28.24 ± 0.81 970 ± 6.4 20 (maltodextrin) + 10 (SiO2) 55.84 ± 0.52 0.94 ± 0.1…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentration of Goji berry polyphenols and carbohydrates in liquid and dried-encapulated Goji berry extract (LGBE and DGBE, respectively), as well as maltodextrin or SiO2 concentration added in liquid Goji berry extracts (LGBE) before encapsulation of the three samples of dried-encapsulated Goji berry powder used in this study. 19.69 ± 0.49 0.65 ± 0.11 3 28.24 ± 0.81 970 ± 6.4 20 (maltodextrin) + 10 (SiO2) 55.84 ± 0.52 0.94 ± 0.1…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings of the present research, it can be suggested that the Goji berry encapsulated extracts could be used as prebiotic additives in food or nutraceuticals, in order to stimulate growth or protect the viability of probiotic strains of Bifidobacterium and Lactobacillus.Microorganisms 2020, 8, 57 2 of 14 lung disorders, and anticancer activity [10][11][12], thanks to which, L. barbarum fruit has recently gained increasing popularity in Europe and North America [12].Recently Goji berries have been also positively evaluated for their prebiotic potential in foods like yogurt [13], since their polysaccharides may be selectively utilized by some probiotic bacteria [14], although a potential prebiotic effect may be also linked to other molecules like polyphenols, which may stimulate the growth of probiotic bacteria in the gut, or inhibit the growth of antagonistic bacteria in the complex intestinal microbiota [15].Gut colonization by beneficial probiotic bacteria is recognized as an essential parameter for intestinal health, and human health in general. It occurs in early life, as Bifidobacterium and Lactobacillus species attach to the gastrointestinal tract, which is necessary for establishing the gut mucosal barrier, maturation and modulation of the immune system, preventing infections by enteric pathogens and improving gastrointestinal function, digestion, and metabolism [16][17][18][19][20]. Nowadays, the presence (or supplementation) of certain probiotic bacteria, prebiotics or symbiotics (mixed preparations of probiotics and prebiotics) in the gastrointestinal tract is linked to prevention or reduced risk of ulcer, gastroenteritis, inflammation, colon cancer and metabolic syndrome (the latter involving hypolipidemic, hypocholesterolemic and potential hypoglycemic activity) as well as preterm birth and neonatal gastrointestinal disorder [21][22][23][24][25][26][27][28][29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Postnatal dietary strategies, including human colostrum/milk or prebiotics/probiotics, reduce morbidities in preterm infants (163). Evidence of prenatal strategies to support reproductive success and fetal health is slowly emerging: modulation of early microbiota in pregnancy shows promising effects (168). Maternal bacteria were shown to enter the gastrointestinal tract of the fetus (169) and microbiota alteration in the neonate and placenta is detectable in pregnant women receiving probiotics (170) but still under debate (14).…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…This contributes to NEC lesions, particularly because the immature intestinal host defences of premature infants predispose them to gut injury . Modulation of gut microbiota may become an efficient preventive approach for NEC pathogenesis …”
mentioning
confidence: 99%